The Concept of Legal Protection in the Implementation of the Complete Systematic Land Registration Program (PTSL) - Zetria Erma (Fox Justi : Jurnal Ilmu Hukum, 2025)
The purpose of this study is to understand and analyze the concept of legal protection in the implementation of the Complete Systematic Land Registration (PTSL) program. This type of research is normative with a statutory approach. The data used are secondary data consisting of primary and secondary legal materials. The research specification used is analytical descriptive. The concept of legal protection in the implementation of systematic land registration (PTSL) is the issuance of land certificates as proof of legitimate ownership, prevention of land disputes, legal certainty regarding land rights, transparency in the land registration process, protection for communities owning land without a certificate, reducing land mafia practices and misuse, guarantees the law for land buyers as well as the right to file a lawsuit against parties that interfere with land rights. PTSL can ensure that landowners' rights are protected by the state, prevent disputes, and reduce the likelihood of abuse of land rights. This program plays an important role in creating legal order in the field of land affairs in Indonesia. Therefore, it is recommended that the government further enhance the protection of landowners in the implementation of PTSL by amending regulations regarding land registration.